2000
DOI: 10.1063/1.481092
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine atom abstraction by Si(100) II. Model

Abstract: A model is developed to describe the kinetics of the three scattering channels-unreactive scattering and dissociative chemisorption via single atom abstraction and two atom adsorption-that are present in the interaction of F 2 with Si͑100͒. The model provides a good description of the non-Langmuirian coverage dependence of the probabilities of single atom abstraction and two atom adsorption, yielding insight into the dynamics of the gas-surface interaction. The statistical model is based on the premise that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
1
19
1
Order By: Relevance
“…5(a). Recent studies of O 2 and F 2 interaction with Si(100) also reported dissociative chemisorption mediated by DBs [12,17,18]. In contrast to Cl 2 , however, the DB merely acts as a catalyst for O 2 dissociation.…”
mentioning
confidence: 99%
“…5(a). Recent studies of O 2 and F 2 interaction with Si(100) also reported dissociative chemisorption mediated by DBs [12,17,18]. In contrast to Cl 2 , however, the DB merely acts as a catalyst for O 2 dissociation.…”
mentioning
confidence: 99%
“…Note that the model reviewed here is a simplified version of the model discussed in Ref. 35, which pertained to the reaction of F 2 on the Si͑100͒ surface. The simplification arises because all nearest neighbor sites on the Al͑111͒ surface are equivalent, whereas on the Si͑100͒ surface, which undergoes a 2ϫ1 reconstruction, they are not.…”
Section: Monte Carlo Algorithmmentioning
confidence: 99%
“…Molecular F 2 has been recently shown to dissociate on Si1002 1 by an atom abstraction mechanism [1][2][3]. This mechanism is distinct from that of classic dissociative chemisorption because a bond of an incident molecule is cleaved upon formation of only a single bond to the surface.…”
mentioning
confidence: 99%